Welcome Manual: Strategy to Promote Happiness Management in the CORPOSUCRE Company of Sincelejo – Sucre. Colombia - Murillo-Montes, Zaida M. (EFIM Ediciones, 2022)
This article stems from an investigation into the management of happiness within the company CORPOSUCRE, in the city of Sincelejo, Sucre. Colombia, which was carried out in order to offer an environment conducive to confluence in labor inclusion and the responsibility assumed with satisfaction by the employees. In the strategy, a Welcome Manual was designed to facilitate the organization, adaptation to change, productivity, the performance of roles and inter-relationship with new workers, in research with a qualitative approach with a hermeneutic cut. Document review was used as a technique for collecting information, and the agenda was used as an instrument. During the investigation, in the institutional planning CORPOSUCRE, strengths were detected in the inclusion of objectives and goals in the short and long term, teamwork, personal and collective responsibility, discipline of trust that contributes to well-being, good customer service and the application of some communication mechanisms of individual and collective management, among the weaknesses is the absence of a physical instrument available to employees to clear up doubts in situations of uncertainty.